A Novel Semi Automated On-Line Determination of Oxonium Ion Via Precipitation Reaction Using a New Mode of Attenuated Measurement of Incident Light (0 – 180o) by AYAH 5SX4-ST-5D Solar CFI Analyser. - M. A. Shakir, Issam; F. A. AL-Razack, Hussein (Iraqi Journal of Science, 2025)
Strong acids were determined via the precipitation reaction of loaded copper (II) ion on strong cation exchange resin which in turn reacts with potassium hyxacyano ferrate (II). The attenuation effect of formed precipitate Cu2 [Fe (CN) 6] on (0 -180o) incident LED light was measurement via homemade AYAH 5SX4-ST-5D solar CFI analyser. Optimum parameters were 0.005M.L-1 [Fe(CN)6]-4 , flow rate of 2.4 mL.min-1 , sample volume 204 μL , sample purge time of 64 seconds was chosen, and 1.6 V for light intensity. A liner calibration graph of 0.005 -0.2 M.L-1 were obtains for HCl, HNO3, HCLO4 and H2SO4, with a linearity (r2 %) 96 -97 % and L.O.D based on gradual dilution of lowest concentration in calibration graph was 37.19 μg for HCl, 64.273 μg for HNO3, 102.26 μg for HCLO4, and 0.01 μg for H2SO4 .Repeatability (RSD %) less than 1.12 was obtained. the proposed was compared well with standard method. FTU method for available acid in commercial ( HCl, H2SO4).